Building the Training and Self-training Skill Model for Vietnamese Students to Meet Enterprises’ Demands - Dang Minh, Nguyen (VNU JOURNAL OF ECONOMICS AND BUSINESS; Vol 34 No 1, 2018)
The effeciency of training and self-training skills play an important role to improve the quality of employees which can meet enterprise’s demand. This research is aimed at investigating the responsiveness of students’skills for the labor market by surveying 50 enterprises. Skills are divided in three groups consisting of technical skills, social skill and cognitive skills. From the survey, authors state that students’ skills are lagging behind the asking of enterprises, especial the social skills. Thus, using the cause analysis, author proposes the training skill model for students to meet enterprises’ demands.